A Review on the Potential Applications for Cadmium Selenide and Graphene Materials - Alghazaly, Saif M.; Neamah, Rusul Mohammed; Funkher, Ahmed Abbood; Al-Seady, Mohammed A. (Journal of Sustainable Materials Processing and Management, 2023)
The unique physical and chemical properties for nanomaterials make them suitable to be used in different applications such as optoelectronic devices, sensors, and biomedical applications. Physical and chemical methods are used to prepare material in nanoscale region. Physical methods depend on the technique used, temperature, and substrate. Cadmium selenide has high sensitive to technique used. Its absorbance and photoluminescence changed with increased size of particles. The surfaces of CdSe can adsorbent different atoms and molecules to saturate dangling bond. Therefore, CdSe nanoparticales are used in chemical and biological sensors. In this review some of recent applications and properties of CdSe are analyzed. Graphene considers one of the important material in the present time, because of unique properties such as high conductivity, high luminance, more hardness materials than diamonds. It is have wide applications in the physical and chemical sensor, also suitable material in the photonic device. In the present review paper we are present the application of graphene materials in the gas sensor and solar cell application.